Antibiotic Resistance, Core-Genome and Protein Expression in IncHI1 Plasmids in Salmonella Typhimurium - Kubasova, Tereza; Cejkova, Darina; Matiasovicova, Jitka; Sekelova, Zuzana; Polansky, Ondrej; Medvecky, Matej; Rychlik, Ivan; Juricova, Helena (Genome biology and evolution, 2016)
Conjugative plasmids from the IncHI1 incompatibility group play an important role in transferring antibiotic resistance in Salmonella Typhimurium. However, knowledge of their genome structure or gene expression is limited. In this study, we determined the complete nucleotide sequences of four IncHI1 plasmids transferring resistance to antibiotics by two different next generation sequencing protocols and protein expression by mass spectrometry. Sequence data including additional 11 IncHI1 plasmids from GenBank were used for the definition of the IncHI1 plasmid core-genome and pan-genome. The core-genome consisted of approximately 123 kbp and 122 genes while the total pan-genome represented approximately 600 kbp. When the core-genome sequences were used for multiple alignments, the 15 tested IncHI1 plasmids were separated into two main lineages. GC content in core-genome genes was around 46% and 50% in accessory genome genes. A multidrug resistance region present in all 4 sequenced plasmids extended over 20 kbp and, except for tet(B), the genes responsible for antibiotic resistance were those with the highest GC content. IncHI1 plasmids therefore represent replicons that evolved in low GC content bacteria. From their original host, they spread to Salmonella and during this spread these plasmids acquired multiple accessory genes including those coding for antibiotic resistance. Antibiotic-resistance genes belonged to genes with the highest level of expression and were constitutively expressed even in the absence of antibiotics. This is the likely mechanism that facilitates host cell survival when antibiotics suddenly emerge in the environment.
Keywords: genom bakteriální; molekulární evoluce; comparative genomic; Humans; proteomics; Host-Pathogen Interactions; Sequence Analysis, DNA; Evolution, Molecular; interakce hostitele a patogenu; lidé; antibakteriální látky; plazmidy; regulace genové exprese u bakterií; sekvenční analýza DNA; Anti-Bacterial Agents; Drug Resistance, Bacterial; salmonelóza; Salmonella typhimurium; IncHI1 plasmids; vysoce účinné nukleotidové sekvenování; Gene Expression Regulation, Bacterial; High-Throughput Nucleotide Sequencing; bakteriální léková rezistence; Genome, Bacterial; Plasmids; Salmonella Infections